Mentorship, Guidance, and Respect for Guiding New Faculty - Christopher Barrick; Michelle Kiec (Academic Chairpersons Conference Proceedings, 2017)
Department chairs wield great power in the career of new faculty. In addition to gatekeeping functions as an evaluator, chairs serve as a role models and senior leaders. Mentorship, guidance, and respect form the foundation for chairs to propel newer faculty to senior department members.
Keywords: new faculty; early career; mentorship; chair; role model